2008
DOI: 10.1523/jneurosci.1744-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Synaptic Receptivity

Abstract: Are neurons born with the ability to form and receive synapses or do they acquire these abilities during development? We have previously found that purified postnatal retinal ganglion cells (RGCs) require soluble astrocyte-derived signals to form synapses in vitro and in vivo. Here we show that newly generated embryonic day 17 (E17) RGCs are able to form but not receive synapses under these conditions. Dendrite growth is not sufficient to trigger receptivity; rather, the ability of newly generated RGCs to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 35 publications
5
64
0
1
Order By: Relevance
“…Control levels were about 8 puncta/neuron (Fig. 7B), which are comparable with values previously reported for retinal ganglion neurons that were also relatively immature and grown in heterochronic co-cultures with astrocytes (10,34). These density values also reflect the fact that counts of puncta are taken in a relatively thin plane at the center of the neuron, and z stacking of images would yield higher values.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Control levels were about 8 puncta/neuron (Fig. 7B), which are comparable with values previously reported for retinal ganglion neurons that were also relatively immature and grown in heterochronic co-cultures with astrocytes (10,34). These density values also reflect the fact that counts of puncta are taken in a relatively thin plane at the center of the neuron, and z stacking of images would yield higher values.…”
Section: Resultssupporting
confidence: 88%
“…Puncta per micrometer of dendrite was estimated using ImageJ software and custom plug-ins as described previously (34). To remove low frequency background from each image, the rolling ball background subtraction was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Punctate colocalization (clusters of proximal pre-and post-synaptic markers on neurites) of PSD-95 and synaptophysin is widely accepted as an indicator of synapses (43,44). Primary human neurons were treated with bryostatin 1or DCPLA-ME alone or after PKC⑀ KD for 10 days.…”
Section: Pkc⑀ Activation Induces Synaptogenesis In Adult Hippocammentioning
confidence: 99%
“…On the other hand, thrombospondisn interact with integrins, potentially supporting the adhesion of glial cells with neurons at the synapse. One investigation using embryonic retinal ganglion neurons has demonstrated that neurons are capable of forming, but not receiving, synapses unless physical contact with astrocytes had been established [79]. The integrin alphaVbeta3 on astrocytes has been shown to bind to a glycoprotein Thy-1 abundantly expressed on neurons [80].…”
Section: Integrins In the Central Nervous Systemmentioning
confidence: 99%